TANTANGAN MENDIDIK GENERASI MILENIAL MUSLIM DI ERA REVOLUSI INDUSTRI 4.0 - Robiatul Adawiyah; Lita Kurnia (Almarhalah, 2022)
ABSTRACTThe Muslim millennial generation is a generation that is quite familiar with the development of information technology, namely they are very good at various applications related to the internet and are active on social media. The rise of digitalization-based data services which is marked by the presence of four things, namely super computers, artificial intelligence, cyber systems and manufacturing collaboration is a revolution from the existence of industry 4.0. the presence of the industrial revolution 4.0 for the world of Islamic education is a challenge for human resources because it requires educators who are innovative and adaptive to technology. This study aims to describe Islamic education which must prepare the Muslim millennial generation to be creative in facing digital challenges directly so that Islamic education can synergize with Industrial Revolution 4.0 education. The research method used is literature review using various data sources such as books, journals, and information about millennial generation education and the development of the industrial revolution 4.0. From the results of the analysis, Islamic education for the Muslim millennial generation must be prepared so that it becomes a generation that is sensitive to technological advances that are deeply rooted in the values and teachings of their religion. Keywords: Education, Muslim Millennial Generation and Industrial Revolution Era 4.0